Investigating a Correlation between Chemoradiotherapy Schedule Parameters and Overall Survival in a real-life LD SCLC Patient Cohort - Manapov, Farkhad; Eze, Chukwuka; Niyazi, Maximilian; Roengvoraphoj, Olarn; Li, Minglun; Hegemann, Nina-Sophie; Hildebrandt, Guido; Fietkau, Rainer; Belka, Claus (Journal of Cancer, 2016)
Background : Chemoradiotherapy (CRT) is a treatment standard in limited disease (LD) small cell lung cancer (SCLC). Currently, the timing of thoracic radiation therapy (TRT) remains the subject of randomised trials and meta-analyses. To investigate a correlation between CRT schedule parameters and overall survival (OS) in a real-life patient cohort, a temporal analysis was performed.Methods: 182 LD SCLC patients successfully treated with definitive CRT were retrospectively reviewed. TRT was applied concurrently or sequentially. Impact of the treatment mode and interval of simultaneous treatment (IST) (an interval in days when chemotherapy and TRT were applied simultaneously, including time between chemotherapy cycles and weekends) on OS was analysed.Results: 71 (39%) patients were treated with concurrent and 111 (61%) with sequential CRT. Median overall survival (MS) for the entire cohort was 534 days (95%CI 461 - 607) without any significant difference between the concurrent and sequential groups (589: 95%CI 358 - 820 vs. 533: 95%CI 446 - 620 days, p=0.746, log-rank test). IST was 0 days in 111 (61%) patients treated sequentially whereas in the concurrent group, 20 (11%) and 51 (28%) patients showed an IST < 35 and > 35 days, respectively. Patients with IST > 0 and < 35 days demonstrated a trend to improved overall survival (MS: IST 0 vs. > 35 vs. < 35 was 533 vs. 448 vs. 1169 days, p=0.109, log-rank test). When patients treated with sequential CRT (IST 0) were excluded from the analysis, statistical difference in overall survival according to the IST subgroups (IST > 35 vs. < 35) became significant (p=0.021, log-rank test). On multivariate analysis of patients treated with concurrent CRT, IST > 0 and < 35 days remained a variable that significantly correlated with better overall survival (p=0.039, HR 0.38).Conclusion: In this real-life LD SCLC patient cohort, improved overall survival was achieved in patients treated with CRT schedule according to the IST > 0 and < 35-day concept. By exceeding the 35-day interval, we have seen deterioration in survival.
EVALuna2:32925